Aspects of the Schwinger Variational Principle Formulation - Lino, J.L.S.; de Farias, A.R.; Araújo, N.S. (Trends in Computational and Applied Mathematics, 2000)
The application of the Schwinger variational principle-SVP and, in particular, the second Born approximation to the evaluation of scattering amplitude and integral cross sections for eletron-atom impact is discussed